Antioxidant activity and protective effect of the outer scales hydroalcoholic extract of Allium cepa L. var. Tropea on toxicity damage induced by Cadmium in Caco-2 cells. (December 2022) - Marrelli, Mariangela; Argentieri, Maria Pia; Alexa, Ersilia; Meleleo, Daniela; Statti, Giancarlo; Avato, Pinarosa; Conforti, Filomena; Mallamaci, Rosanna
Abstract: The characterization of bioactive metabolites and the protective effects against Cadmium (Cd) of the hydroalcoholic extract from Allium cepa var. Tropea (Tropea red onion) in human Caco-2 colon adenocarcinoma cells and in vitro antioxidant effects were investigated. Tropea red onion extract showed high levels of bioactive compounds and a strong activity as radical scavenger and inhibitor of lipid peroxidation. The most abundant specialized metabolites were quercetin derivatives. In addition, the extract inhibited NO release in a dose-dependent manner. Exposure of Cd treated human Caco-2 cells to the Tropea red onion extract resulted in a higher cytoprotection with a significant falloff of cells damage produced by Cd. The effect of Tropea red onion evaluated with the MTT assay and LDH test, was time-dependent and more evident after 24h of treatment. Caco-2 cells treated with the Tropea red onion extract and CdCl2 at 24h showed a significant cytoprotection at concentrations equal to 50 μg/mL + 25 μM and 100 μg/mL + 25 μM while at 72h at a concentration of 25 μg/mL + 25 μM. We observed with MTT and LDH assays that treatment of cells with Tropea red onion extract at 24h was able to significantly prevent Cd-induced cytotoxicity alone. Graphical abstract: Image 1 Highlights: Cadmium is one of the most toxic environmental pollutant. Phytochemical and biological characterization of Tropea red onion. Tropea red onion extract prevent Cd-induced cytotoxicity in human adenocarcinoma.